Fabrication and characterization of semiconductor gas senors by Metallo-Organic Decomposition (MOD) and thick film technology - Zhu, Weiguang (2008)
In the report, the application of new sensing material and the material processing technology routes were discussed. Firstly, in the application of ferroelectric materials for hydrogen gas detection, a new metal-ferroelectric (MF) interface sensor structure has been designed, fabricated and characterized. Secondly, the work on the semiconductor iron oxide Fe203-based thick film gas sensor aims to improve on the gas sensing performance through the use of a different material processing technique.